Audit Delay serta Faktor Internal Perusahaan : Studi Kasus Perusahaan Trade, Service, and Investment - Devi Dwi Yanti; Rollickus Elta Zagoto; Wenny Anggresia Ginting (Owner : Riset dan Jurnal Akuntansi, 2021)
The announcement from the Indonesia Stock Exchange on april 11, 2018, revealed that 70 companies have not submitted audited financial statements as of December 31, 2017, six of which are included in the trade, service, and investment sectors. Facts related to the rise of companies experiencing audit delays have been researched by several studies, but there are differences in results between researchers. Analyzing the effect of solvency, company size, company age, and audit opinions on audit delays is a research objective. The approach applied is the quantitative research method. The data processed comes from the website of the Indonesia Stock Exchange. The population in this study was 119 and a sample of 72 companies that are listed on the Indonesia Stock Exchange trade, service, and investment sector where the selection of samples using purposive sampling. The method used for statistical testing is the Logistic Regression and obtained solvency results, company size, and audit opinion do not affect audit delay, while the age of the company affects audit delay. The limitation of the research is to only process data based on data from the official website of the indonesia stock exchange trade, service, and investment sector for the period 2017-2019 and focus on research variables. This research is expected to be input and consideration for companies to report their report on time and for investors to be considered to decide their investment decisions and can contribute to filling the literature gap related to audit delay with the latest data 2017-2019.